The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2009
DOI: 10.1021/jp909517r
|View full text |Cite
|
Sign up to set email alerts
|

Vibrational Analysis of Amino Acids and Short Peptides in Hydrated Media. VI. Amino Acids with Positively Charged Side Chains: l-Lysine and l-Arginine

Abstract: In two recent reports of the same series (J. Phys. Chem. B 2007, 111, 1470-1477 and J. Phys. Chem. B 2009, 113, 3169-3178), we have described the geometrical and vibrational analysis of glycine and amino acids (AAs) with hydrophobic side chains through the joint use of optical spectroscopy and quantum mechanical calculations. Here, we report Raman scattering and Fourier-Transform Infrared (FT-IR) Attenuated Total Reflectance (ATR) spectra measured from the aqueous solutions (H(2)O and D(2)O) of L-lysine and L-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
83
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(89 citation statements)
references
References 30 publications
(102 reference statements)
4
83
0
2
Order By: Relevance
“…A broad band at 849 cm −1 in the spectra of solution can be found. The band assignments [24] for lysine are listed in Table 8.…”
Section: Basic Amino Acidsmentioning
confidence: 99%
See 1 more Smart Citation
“…A broad band at 849 cm −1 in the spectra of solution can be found. The band assignments [24] for lysine are listed in Table 8.…”
Section: Basic Amino Acidsmentioning
confidence: 99%
“…Assignment * (PED) [24] 1477 1470 Cı-bend (72); C -bend (11) 1443 1445 NÁ1-C-NÁ2 asym st (24); Cı-Nε-Hε (22) …”
mentioning
confidence: 99%
“…Almost no work on Raman spectroscopy of l-lysine was published. However, Hernández et al [ 0] showed the assignment of the main modes of the Raman spectrum of l-lysine. For example, the stretching of CC is observed at 1012, 1033, 1063, and 10 6 cm l-histidine was investigated through Raman spectroscopy in a recent paper that explored the vibrational behavior of the crystal under cryogenic conditions [ 1].…”
Section: Neutral Polar Amino Acidsmentioning
confidence: 99%
“…30 Arginine has been shown to have two bands observed at 1586 and 1608 cm -1 due to the asymmetrical vibrations of the CN bonds of the guanidine group. Although these two overlapping bands are not always clearly observable, 3 they have been well characterized in the linear infrared spectra. 1,2,6 The interactions of these side chains with counterions and their involvement in salt bridge formation result in significant changes in the linear spectrum.…”
Section: Introductionmentioning
confidence: 99%